Pharmacological and non-pharmacological treatments and outcomes for new-onset atrial fibrillation in ICU patients: the CAFE scoping review and database analyses - Bedford, J; Drikite, L; Corbett, M; Doidge, J; Ferrando-Vivas, P; Johnson, A; Rajappan, K; Mouncey, P; Harrison, D; Young, D; Rowan, K; Watkinson, P (National Institute for Health Research, 2021)
Background New-onset atrial fibrillation occurs in around 10% of adults treated in an intensive care unit. New-onset atrial fibrillation may lead to cardiovascular instability and thromboembolism, and has been independently associated with increased length of hospital stay and mortality. The long-term consequences are unclear. Current practice guidance is based on patients outside the intensive care unit; however, new-onset atrial fibrillation that develops while in an intensive care unit differs in its causes and the risks and clinical effectiveness of treatments. The lack of evidence on new-onset atrial fibrillation treatment or long-term outcomes in intensive care units means that practice varies. Identifying optimal treatment strategies and defining long-term outcomes are critical to improving care. Objectives In patients treated in an intensive care unit, the objectives were to (1) evaluate existing evidence for the clinical effectiveness and safety of pharmacological and non-pharmacological new-onset atrial fibrillation treatments, (2) compare the use and clinical effectiveness of pharmacological and non-pharmacological new-onset atrial fibrillation treatments, and (3) determine outcomes associated with new-onset atrial fibrillation. Methods We undertook a scoping review that included studies of interventions for treatment or prevention of new-onset atrial fibrillation involving adults in general intensive care units. To investigate the long-term outcomes associated with new-onset atrial fibrillation, we carried out a retrospective cohort study using English national intensive care audit data linked to national hospital episode and outcome data. To analyse the clinical effectiveness of different new-onset atrial fibrillation treatments, we undertook a retrospective cohort study of two large intensive care unit databases in the USA and the UK. Results Existing evidence was generally of low quality, with limited data suggesting that beta-blockers might be more effective than amiodarone for converting new-onset atrial fibrillation to sinus rhythm and for reducing mortality. Using linked audit data, we showed that patients developing new-onset atrial fibrillation have more comorbidities than those who do not. After controlling for these differences, patients with new-onset atrial fibrillation had substantially higher mortality in hospital and during the first 90 days after discharge (adjusted odds ratio 2.32, 95% confidence interval 2.16 to 2.48; adjusted hazard ratio 1.46, 95% confidence interval 1.26 to 1.70, respectively), and higher rates of subsequent hospitalisation with atrial fibrillation, stroke and heart failure (adjusted cause-specific hazard ratio 5.86, 95% confidence interval 5.33 to 6.44; adjusted cause-specific hazard ratio 1.47, 95% confidence interval 1.12 to 1.93; and adjusted cause-specific hazard ratio 1.28, 95% confidence interval 1.14 to 1.44, respectively), than patients who did not have new-onset atrial fibrillation. From intensive care unit data, we found that new-onset atrial fibrillation occurred in 952 out of 8367 (11.4%) UK and 1065 out of 18,559 (5.7%) US intensive care unit patients in our study. The median time to onset of new-onset atrial fibrillation in patients who received treatment was 40 hours, with a median duration of 14.4 hours. The clinical characteristics of patients developing new-onset atrial fibrillation were similar in both databases. New-onset atrial fibrillation was associated with significant average reductions in systolic blood pressure of 5 mmHg, despite significant increases in vasoactive medication (vasoactive-inotropic score increase of 2.3; p < 0.001). After adjustment, intravenous beta-blockers were not more effective than amiodarone in achieving rate control (adjusted hazard ratio 1.14, 95% confidence interval 0.91 to 1.44) or rhythm control (adjusted hazard ratio 0.86, 95% confidence interval 0.67 to 1.11). Digoxin therapy was associated with a lower probability of achieving rate control (adjusted hazard ratio 0.52, 95% confidence interval 0.32 to 0.86) and calcium channel blocker therapy was associated with a lower probability of achieving rhythm control (adjusted hazard ratio 0.56, 95% confidence interval 0.39 to 0.79) than amiodarone. Findings were consistent across both the combined and the individual database analyses. Conclusions Existing evidence for new-onset atrial fibrillation management in intensive care unit patients is limited. New-onset atrial fibrillation in these patients is common and is associated with significant short- and long-term complications. Beta-blockers and amiodarone appear to be similarly effective in achieving cardiovascular control, but digoxin and calcium channel blockers appear to be inferior. Future work Our findings suggest that a randomised controlled trial of amiodarone and beta-blockers for management of new-onset atrial fibrillation in critically ill patients should be undertaken. Studies should also be undertaken to provide evidence for or against anticoagulation for patients who develop new-onset atrial fibrillation in intensive care units. Finally, given that readmission with heart failure and thromboembolism increases following an episode of new-onset atrial fibrillation while in an intensive care unit, a prospective cohort study to demonstrate the incidence of atrial fibrillation and/or left ventricular dysfunction at hospital discharge and at 3 months following the development of new-onset atrial fibrillation should be undertaken. Trial registration Current Controlled Trials ISRCTN13252515. Funding This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 25, No. 71. See the NIHR Journals Library website for further project information.